FACTORS AFFECTING MSME INCOME IN PAGUYAMAN DISTRICT - Marmawira Rajak; Fibriyanti Lakoro; Rizal (Journal of Economic, Business, and Administration (JEBA), 2022)
The purpose of this study was to determine the factors that influence the income of MSMEs in Paguyaman District, Boalemo Regency. T he method in this research is qualitative with a descriptive approach. The types and sources of data used are primary data and secondary data. The data analysis technique used in this study uses interactive analysis. The results of the study show the following: (1) Capital is a very supportive factor in increasing MSME income, although not all MSMEs in the sub-district have sufficient capital to increase income. (2) The length of business is a support in increasing income because a long-running business is very helpful in increasing income. (3) The number of workers has not been supported in increasing income in MSMEs in Paguyaman District this is because there are still many MSMEs that are classified as small. (4) Business location has not become a supporting factor in increasing income because there are still many MSMEs that do not yet have a strategic location. (5) Operational hours are not a supporting factor in increasing income, considering that MSMEs in Paguyaman District have different Operating Hours. (6) The achievement of the target is one of the supporters in increasing the income of MSMEs in the Paguyaman sub-district. (7) Work experience has not fully supported the income because MSMEs in Paguyaman District do not need experienced employees.